2015
DOI: 10.1002/hed.23952
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of negative pressure wound therapy and conventional dressing methods for fibula free flap donor site management in patients with head and neck cancer

Abstract: The use of negative pressure wound therapy for fibula free flap donor site management facilitates early patient mobilization, ensures better graft acceptance, and significantly decreases the healing time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Previous groups have recommended that donor sites with width of less than 4 cm can be closed safely without tension although this will vary with skin laxity [ 5 , 6 ]. Other techniques to reduce wound healing problems include using negative pressure wound therapy over skin grafts and the harvest of a fat-fascia only flap in order to enable primary closure [ 7 , 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous groups have recommended that donor sites with width of less than 4 cm can be closed safely without tension although this will vary with skin laxity [ 5 , 6 ]. Other techniques to reduce wound healing problems include using negative pressure wound therapy over skin grafts and the harvest of a fat-fascia only flap in order to enable primary closure [ 7 , 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…Open healing of the fibular donor site and meshing of the surrounded tissue has been reported as a modification to decrease the wound area and avoid the morbidity associated with graft and resulted in a good cosmetic outcome ( 99 ). The use of vacuum-assisted closure allows patients to be mobilized sooner, assures greater graft acceptance, and reduces healing time up to 50% ( 100 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, though the use of negative-pressure therapy has resulted in a shortened healing period, they also demonstrated that the time of total healing of skin grafts can still be extensive, and has been reported from 67 days to as long as 163 days. 25 The use of a wound vac can also add a significant amount of cost to the postoperative care, with cost of the devices themselves, as well as home health care nurses for vac and/or dressing changes, and the cost of the dressing materials themselves. The use of PFPFs has been used extensively in lower extremity reconstruction, 26 and since its introduction has undergone multiple modifications and adaptations for different uses in reconstructive surgery.…”
Section: Discussionmentioning
confidence: 99%